Sistem Informasi Monitoring Komoditas Sayur untuk Penentuan Harga Wajar Menggunakan Metode Standar Deviasi - Muh Zia Ulkhaq; Rifki Figianto; Luthfi Nur Azizah (Bulletin of Computer Science Research, 2026)
The dynamic fluctuation of vegetable commodity prices often creates uncertainty in determining fair prices in traditional markets. This condition leads to information asymmetry between traders, buyers, and market managers, requiring a more objective approach to define fair price boundaries. This study aims to develop a statistical-based price monitoring model to identify a more measurable fair price range for vegetable commodities. The method used in this study is standard deviation as a statistical tool to measure the level of price dispersion based on historical price data. The mean and standard deviation values are used to construct the lower and upper bounds of the fair price range using the mean ± 1? approach. The data used in this study were obtained from the red chili commodity at the Banjarnegara Main Market as a case study.The results show that the standard deviation method is able to objectively represent price variability and classify market conditions into three categories, namely low price, normal price, and high price, based on the position of prices relative to the statistical range. In the case study of April 2026, the mean price was Rp63,300/kg and the standard deviation was Rp6,830/kg, resulting in a fair price range between Rp56,470/kg and Rp70,130/kg. This study concludes that the standard deviation approach is effective in identifying fair price boundaries based on historical data. The main contribution of this research is the development of a more objective price analysis model to support price transparency in traditional markets.